2019
DOI: 10.1038/s41375-019-0404-1
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Wnt signaling in multiple myeloma: molecular mechanisms and targeting options

Abstract: Aberrant activation of Wnt/β-catenin signaling plays a central role in the pathogenesis of a wide variety of malignancies and is typically caused by mutations in core Wnt pathway components driving constitutive, ligand-independent signaling. In multiple myelomas (MMs), however, these pathway intrinsic mutations are rare despite the fact that most tumors display aberrant Wnt pathway activity. Recent studies indicate that this activation is caused by genetic and epigenetic lesions of Wnt regulatory components, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 108 publications
1
120
0
1
Order By: Relevance
“…Among them, the WNT pathway is deregulated in epithelial-mesenchymal transition (EMT) and CSCs (13). Mutations in WNT signaling components, such as APC, AXIN, β-catenin, and WNT ligands were first observed in colorectal cancers, but have also been reported in other solid tumors (14)(15)(16)(17)(18)(19)(20)(21) and hematological malignancies, including leukemia and Multiple Myeloma (MM) (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the WNT pathway is deregulated in epithelial-mesenchymal transition (EMT) and CSCs (13). Mutations in WNT signaling components, such as APC, AXIN, β-catenin, and WNT ligands were first observed in colorectal cancers, but have also been reported in other solid tumors (14)(15)(16)(17)(18)(19)(20)(21) and hematological malignancies, including leukemia and Multiple Myeloma (MM) (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] The aberrant activation of the Wnt/β-catenin pathway with nonphosphorylated active β-catenin expression in the nucleus could sensitize MM cells to autocrine Wnt ligands and paracrine Wnt emanating from the BMM, thus may contribute to the proliferation, migration, and drug resistance of MM cells (see recent review). 29 The results presented in Figure 5C revealed that β-catenin protein levels were downregulated following HK-11 treatment and that this suppressive effect could be reversed by LiCl, which stabilized β-catenin by inhibiting the kinase activity of Glycogen Synthase Kinase-3, a crucial mediator of the Wnt/β-catenin signaling. 24,30 It has been suggested that the inhibitory effect of HK-11 on β-catenin signaling may be utilized as a potential target for treating MM, as the majority of MM patients exhibit hallmarks of Wnt activation in a ligand- dependent manner, irrespective of the complex genetic heterogeneity.…”
Section: Discussionmentioning
confidence: 91%
“…24,30 It has been suggested that the inhibitory effect of HK-11 on β-catenin signaling may be utilized as a potential target for treating MM, as the majority of MM patients exhibit hallmarks of Wnt activation in a ligand- dependent manner, irrespective of the complex genetic heterogeneity. 29 Furthermore, β-catenin is dynamically stored and cleared in MM. 31 Further studies are required to investigate the most effective strategy for targeting canonical Wnt signaling in MM, potentially by inhibiting Wnt/βcatenin activation in the BMM of MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher processes through activation of canonical Wnt/βcatenin pathway and non-canonical pathways [9,10]. Wnt5a, a member of Wnt family, plays various physiological roles in tumor growth, invasion and metastasis, mainly by activating the non-canonical pathways such as planar cell polarity (PCP), JNK and Ca2 + /CaKMII pathways [11,12].…”
Section: Ivyspringmentioning
confidence: 99%